Dynamic adapter generation for data integration middleware. - Gong, Peng (Software engineering notes.)
Relatively mature integration technologies are available that make application integration tractable from an engineering perspective. However, integrating multiple heterogeneous data sources into applications is still a time-consuming, costly and error-prone engineering task, because existing integration technologies are based on static integration architectures. Such architectures tightly couple a data source to the data integration infrastructure. This paper describes the architecture and evolving prototype implementation of the Data Concierge, which provides a dynamic solution to integrate heterogeneous data sources. The core architecture and mechanisms in the Data Concierge can be used for dynamically attaching to a previously unidentified source of information, without the need for a pre-existing adapter component. In this paper, an ontology based API description mechanism supported by the Data Concierge is described, along with the architecture and prototype tools for describing the metadata necessary to facilitate dynamic integration. The use of an ontology and associated state machine to generate API calls to access data sources is illustrated using an FTP data source.